Open globe injury in children: Prognostic factors - Flores-Boza, Abel (2013)
Objective: to identify prognostic factors for visual acuity after repair of open globe injuries in children. Methods: retrospective study by reviewing records of 25 patients, aged 14 years or younger at the Instituto Nacional de Oftalmología Perú. Results: the mean age was 6,7 years. 68,2 % were male children. Objects most often causing penetrating injury were scissors, glasses and needles (52,0 %). 72,0 % of children developed traumatic cataract. Additional surgery was performed in 16,0 % of cases. Final visual acuity was: light perception/ hand motion in 24 % of cases, count fingers acuity in 20 %, and 20/200 or better in 56% of cases. Conclusions: factors suggesting unfavourable final visual acuity after open globe injuries in children are: poor initial visual acuity, wound length >10 mm and vitreous prolapsed at presentation.